Lorlatinib in pretreated ALK- or ROS1-positive lung cancer and impact of TP53 co-mutations: results from the German early access program. (February 2021) - Frost, Nikolaj; Christopoulos, Petros; Kauffmann-Guerrero, Diego; Stratmann, Jan; Riedel, Richard; Schaefer, Monica; Alt, Jürgen; Gütz, Sylvia; Christoph, Daniel C.; Laack, Eckart; Faehling, Martin; Fischer, Richard; et al.
Introduction: We report on the results of the German early access program (EAP) with the third-generation ALK- and ROS1-inhibitor lorlatinib. Patients and Methods: Patients with documented treatment failure of all approved ALK/ROS1-specific therapies or with resistance mutations not covered by approved inhibitors or leptomeningeal carcinomatosis were enrolled and analyzed. Results: In total, 52 patients were included [median age 57 years (range 32–81), 54% female, 62% never smokers, 98% adenocarcinoma]; 71% and 29% were ALK- and ROS1-positive, respectively. G1202R and G2032R resistance mutations prior to treatment with lorlatinib were observed in 10 of 26 evaluable patients (39%), 11 of 39 patients showed TP53 mutations (28%). Thirty-six patients (69%) had active brain metastases (BM) and nine (17%) leptomeningeal carcinomatosis when entering the EAP. Median number of prior specific TKIs was 3 (range 1–4). Median duration of treatment, progression-free survival (PFS), response rate and time to treatment failure were 10.4 months, 8.0 months, 54% and 13.0 months. Calculated 12-, 18- and 24-months survival rates were 65, 54 and 47%, overall survival since primary diagnosis (OS2) reached 79.6 months. TP53 mutations were associated with a substantially reduced PFS (3.7 versus 10.8 month, HR 3.3, p = 0.003) and were also identified as a strong prognostic biomarker (HR for OS2 3.0 p = 0.02). Neither prior treatments with second-generation TKIs nor BM had a significant influence on PFS and OS. Conclusions: Our data from real-life practice demonstrate the efficacy of lorlatinib in mostly heavily pretreated patients, providing a clinically meaningful option for patients with resistance mutations not covered by other targeted therapies and those with BM or leptomeningeal carcinomatosis.